Impaired Visual Cortical Processing of Affective Facial Information in Schizophrenia. (July 2016) - Maher, Stephen; Ekstrom, Tor; Chen, Yue
Facial-emotion-perception impairment in schizophrenia is currently viewed as abnormal affective processing. Facial-emotion perception also relies on visual processing. Yet visual cortical processing of facial emotion is not well understood in this disorder. We measured perceptual thresholds for detecting facial fear and happiness in patients ( n = 23) and control participants ( n = 23) and adjusted emotion intensity of facial stimuli (via morphing between images of neutral and emotive expressions) for each participant. We then evaluated activations of the visual cortex and amygdala during the performance of perceptually equated facial-emotion-detection tasks. Patients had significantly lower fear- and happiness-induced activations in the visual cortex and amygdala. Activations between the visual cortex and amygdala were largely correlated, but the correlations in patients occurred abnormally early in the response time course during fear perception. In schizophrenia, visual processing of facial emotion is deficient, and visual and affective processing of negative facial emotion may be prematurely associated.